Historic Hotel Times (Cimarron, New Mexico Cimarron Legend)
Advertisement for Historic Hotel Time which is an exclusive production of the One Horse Publishing Co. of Cimarron, New Mexico.
Master List item # 28
File location is in the Raton File Cabinet
Keywords: Historic Hotel Times; The One Horse Publishing Co; Cimarron Legend; Newspaper; Cimarron, New Mexico